The Pengaruh Work Life Balance terhadap Kinerja Karyawan di Hotel ORB - Wita Indrayani, I Gusti Ayu Putu; Wulan Dari, Ni Wayan; Adinda, Clearesta (Journal of Hotel Management, 2025)
Human resource management, especially employee performance, is an important emphasis that must be paid attention to by companies. However, what is no less important is the employee's work life balance in managing the quality of his life against the demands of work and life outside of work which must be considered in order to maintain his performance. This research was conducted at Hotel ORB. This research aims to determine the effect of work life balance on employee performance which is analyzed using the Statistical Program for Social Science (SPSS). The type of data needed by researchers uses quantitative data with data collection techniques, namely questionnaires. The population in this study involved all employees at Hotel ORB, totaling 183 people. The sample used in this research was 126 respondents. The sampling technique is probability sampling technique (proportinate stratified random sampling) because the population is heterogeneous. The results of this research show that work life balance simultaneously has a positive and significant effect, with a tcount>ttable value of 6.529>0.1743. Work life balance contributes to influencing employee performance by 60.6% and the remaining 39.4% is influenced by other variables not used in this research.